علاقة استخدام " الكتاب المقرر لمهارة الاستماع " نحو ترقية مهارة الاستماع - Dimyathi, Muhammad Afifuddin; Syafi'i; Arofat, Husnul; Nisa’, Khoirun; Maghfuri, Ali (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
This study aims to improve listening skills by using textbooks as a reference in practicing students' listening skills. textbooks cannot be separated from students in formal learning at school. special skills' is also a very difficult skill of the 4 existing skills. and writing this article aims to test or try the textbook whether it can help improve students' listening skills or vice versa can not help improve and facilitate students in learning Arabic. and the discussion of this package book is also equipped with a listening learning CD and there are also basic competencies and the latest achievement indicators in each material.